Variations of fine particle physiochemical properties during a heavy haze episode in the winter of Beijing - Niu, H. Y.; Hu, W.; Zhang, D. Z.; ZJ Wu; Guo, S.; Pian, W.; Cheng, W. J.; Min* Hu (Science of the Total Environment, 2016)
Chemical composition, morphology, size and mixture of fine particles were measured in a heavy haze and the post-haze air in Beijing in January 2012. With the occurrence of haze, the concentrations of gaseous and particulate pollutants including organics, sulfate, nitrate, and ammonium grew gradually. The hourly averaged PM2.5 concentration increased from 118 mu g m(-3) to 402 mu g m(-3) within 12 h. In contrast, it was less than 10 mu g m(-3) in the post-haze air. Occupying approximately 46% in mass, organics were the major component of PM1 in both the haze and post-haze air.Analysis of individual particles in the size range of 0.2-1.1 mu m revealed that secondary-like particles and soot particles were always the majority, and most soot particles had a core-shell structure. The number ratio of secondary-like particles to soot particles in accumulation mode in the haze air was about 2:1, and that in the post-haze air was 8:1. These results indicate both secondary particle formation and primary emission contributed substantially to the haze. The mode size of the haze particles was about 0.7 mu m, and the mode size of the post-haze particles was 0.4 mu m, indicating the remarkable growth of particles in haze. However, the ratios of the core size to shell size of core-shell structure soot particles in the haze were similar to those in the post-haze air, suggesting a quick aging of soot particles in either the haze air or the post-haze air. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: aerosol mass-spectrometry; aging; aging timescale; black carbon; chemical-composition; core-shell structure; inorganic aerosols; morphology; north china plain; organic aerosols; relative-humidity; secondary formation; secondary particles; size; soot particles